Relationship between Organizational Climate and Teachers' Work Productivity - Susanti, Eni; Indrati, Briliantina (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2023)
This study aims to find strategies and ways to increase teacher work productivity by examining the strength of the relationship between work productivity and visionary leadership. This study uses a sequential explanatory design, using correlational statistical methods. With a research sample of 252 PNS teachers in Depok City State Junior High School. Based on the results of the study that there is a significant positive relationship between Organizational Climate and Work Productivity with correlation coefficient ry2 = 0.698, so strengthening Organizational Climate can increase work productivity.